2016
DOI: 10.1120/jacmp.v17i2.5690
|View full text |Cite
|
Sign up to set email alerts
|

Diamond detector in absorbed dose measurements in high‐energy linear accelerator photon and electron beams

Abstract: Diamond detectors (DD) are preferred in small field dosimetry of radiation beams because of small dose profile penumbras, better spatial resolution, and tissue‐equivalent properties. We investigated a commercially available ‘microdiamond’ detector in realizing absorbed dose from first principles. A microdiamond detector, type TM 60019 with tandem electrometer is used to measure absorbed doses in water, nylon, and PMMA phantoms. With sensitive volume 0.004 mm3, radius 1.1 mm, thickness 1×10−3mm, the nominal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…5,6 In addition, diamond's atomic number is close to the effective atomic number (Z) of water/tissue, resulting in a relatively low-energy dependence for beam energies used within the therapeutic range, theoretically. 7 When ionizing radiation passes through the DD, electronhole pairs are generated, and collected with an electric field. This collected ionization current is directly proportional to the incoming ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 In addition, diamond's atomic number is close to the effective atomic number (Z) of water/tissue, resulting in a relatively low-energy dependence for beam energies used within the therapeutic range, theoretically. 7 When ionizing radiation passes through the DD, electronhole pairs are generated, and collected with an electric field. This collected ionization current is directly proportional to the incoming ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, diamond detectors are highly resistant to radiation damage (0.05% loss in sensitivity per kGy) and have excellent spatial resolution (4 mm2 active measurement area and 1 μ m thickness) 5,6 . In addition, diamond’s atomic number is close to the effective atomic number (Z) of water/tissue, resulting in a relatively low‐energy dependence for beam energies used within the therapeutic range, theoretically 7 …”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study was to find a stable measurement point of clinical interest to validate the accuracy of the CyberKnife MultiPlan planning system on a small static field, with particular focus on small cone sizes less than 20 mm using suitable detectors. Plastic scintillation devices (PSD) have been studied for more than 20 yr, and several recent publications have shown that in small fields their performance compares favorably to other detectors including stereotactic diodes, microchambers, and synthetic diamond detectors . Moreover, their properties of tissue equivalence, linearity, energy dependence, small correction factor in homogeneous media, make them an attractive candidate for small field validation in heterogeneous media.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one must know the stopping power and range values for such materials. Besides developing the new dosimeter materials, it is also important to know the stopping power and range values for the estimating the obtained dose by target [2,3], this makes possible to estimate the effect of the electron beams in the target. These values determined or read from the database in the radiation therapy systems.…”
Section: Introductionmentioning
confidence: 99%